Fish Movement Mapping as a Basis for Programming Circulation Systems in Traditional Market Building - Rachmadika, Alifian; Harani, Arnis Rochma; Riskiyanto, Resza (MAJ - Malaysia Architectural Journal, 2023)
This article explores the use of big data in the preparation of architectural programs, especially in the programming the circulation in the case of traditional market buildings. Current technological developments require movement in all aspects to follow and adapt to various information processes and allow reading and use of the data as a consideration for decision-making, one of which is in the field of architecture. Using big data has begun to develop as a component in compiling and designing architectural programming, but just a few discussed how to read big data as a guide for the development of a circulation system in a building. This article examines the potential for developing a circulation system based on big data. This article attempts to explore various types of data related to a fish movement which are then read from the data used as keywords in the preparation of the circulation system. This article is not in the position of seeing big data as a prediction, but as a description, so it is not fixated on data attachment and the architectural program to be developed. The method used is to collect various data from the internet and some literature. Then to get the results of data reading carried out the method but as a description so that it is not fixated on data attachment and the architecture program to be developed. The method used is to collect various data from the internet and some literature. Then to get the results of data reading carried out the method but as a description so that it is not fixated on data attachment and the architecture program to be developed. Then to get the results of the data reading carried out the method tracing each fish movement mapping data. Then the tracing results are analyzed with in-depth interpretation. The findings in this article show that reading big data, especially reading fish movements, finding the patterns: (1) spreading (2) merging (3) rotating (4) linear (5) gathering. This pattern used further as a keyword for developing a circulation system in the traditional market building. The development of the circulation system is carried out by focusing on the patterns that are present in the collected big data. This article can add insight into architectural programming approaches, especially the use of big data as a design basis.